Lifehacking and Biohacking trends driven by the pandemic of covid-19 and fashion - Sena, Taisa Vieira (2021)
The research of trends, which is more relevant nowadays, concerns observations andconsiderations about the consumer society, mainly in the new nuclei and niches ofconsumption. Different authors claim that prospective research professionals map severalareas of predominance currently on the scene and evaluate their main implications forthe future. Trend research looks at people’s behavior and the context in which it happens.Although people were already gaining more and more space and interest, the search forcontent related to lifekacking and biohacking expanded significantly during the Covid-19pandemic. In this sense, the research seeks to analyze how this specific moment and contextcould boost these behavioral trends and reflect on possible impacts on fashion.